Unraveling Learning Difficulties in Biology Among Class VIII Students at SMP Negeri 19 Palu - Eka Hardiyanti R. Batania; Musdalifah Nurdin; Amalia Buntu (Equator Science Journal, 2025)
This research aims to identify the learning difficulties of 8th-grade students in Science (Biology) at SMP Negeri 19 Palu. This type of research is descriptive. The subjects in this research were all students of classes VIII A and VIII B, consisting of 46 students. The data collection technique used was a questionnaire on factors influencing students' learning difficulties. The results of the study showed that the average internal difficulty factor for the "agree" response was 27%, while "disagree" was 73%. For the external difficulty factor, the "agree" response was 31%, while "disagree" was 69%. These results indicate that students' learning difficulties are classified as high in both internal and external factors. Therefore, it can be concluded that both external and internal factors significantly contribute to the high level of learning difficulties in the Science subject at SMP Negeri 19 Palu.